2017
DOI: 10.3390/en10111767
|View full text |Cite
|
Sign up to set email alerts
|

Heat Modeling and Material Development of Mg-Based Nanomaterials Combined with Solid Oxide Fuel Cell for Stationary Energy Storage

Abstract: Mg-based materials have been investigated as hydrogen storage materials, especially for possible onboard storage in fuel cell vehicles for decades. Recently, with the development of large-scale fuel cell technologies, the development of Mg-based materials as stationary storage to supply hydrogen to fuel-cell components and provide electricity and heat is becoming increasingly promising. In this work, numerical analysis of heat balance management for stationary solid oxide fuel cell (SOFC) systems combined with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Emerging ideas, such as new composite materials, metastable alloys, geometrical storage materials, as well as nano-confinement technology, may give us some new directions to develop Mg-based hydrogen storage materials in the future. On the other hand, Mg-based nanomaterials combined with solid oxide fuel cells for stationary energy storage have been proposed, and this makes it possible to apply Mg-based hydrogen storage materials to large-scale storage with a working temperature for storage materials higher than 250 • C [43]. In this case, thermodynamic change is no longer a problem.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Emerging ideas, such as new composite materials, metastable alloys, geometrical storage materials, as well as nano-confinement technology, may give us some new directions to develop Mg-based hydrogen storage materials in the future. On the other hand, Mg-based nanomaterials combined with solid oxide fuel cells for stationary energy storage have been proposed, and this makes it possible to apply Mg-based hydrogen storage materials to large-scale storage with a working temperature for storage materials higher than 250 • C [43]. In this case, thermodynamic change is no longer a problem.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that reducing the size of hydrogen storage materials could lead to a remarkable change in hydrogen absorption/desorption kinetics [12,[38][39][40][41]. It is well proven that small particles of hydrides have an influence on hydrogen absorption/desorption kinetic properties, mainly due to shortened hydrogen diffusion and dissociation pathways, and enlarged surface free energy when the size decreases to below a few nanometers [42,43]. Numerous methods are applied to synthesize the hydrogen storage nanostructured materials, including ball milling, the hydrogen plasma metal reaction, nano-confinement, thin film synthesis, and catalyzed solution synthesis.…”
Section: Effect Of Downsizing On Kineticsmentioning
confidence: 99%
“…In the hydrogen storage area, Mg-based materials are promising candidates due to the large abundant reserve in the crust, the light weight of Mg element, and high hydrogen storage capacity (7.6 wt % for Mg) [34][35][36]. However, the relatively higher hydrogen desorption enthalpy (74.6 kJ/mol, from Sandia National Lab database) becomes a restriction for the future application of Mg-based materials for hydrogen storage [35,37,38]. The story is totally different when Mg-based materials are applied to TES.…”
Section: Different Heat Storage Systems Of Mg-based Materialsmentioning
confidence: 99%
“…In TES systems, Mg‐based phase change heat storage alloy has the advantage of low corrosion at high temperatures, which are better than Al‐based alloys in comparison. Currently, researchers have focused more on the Mg‐based phase change heat storage alloy as TES materials, and have conducted a lot of research 19‐24 . For instance, Faik et al 25 investigated the structure and thermophysical properties of Zn 85.8 Al 8.2 Mg 6 and Mg 70 Zn 24.9 Al 5.1 eutectic alloys, and found that the great potential of the alloys studied in heat energy storage applications.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, researchers have focused more on the Mg-based phase change heat storage alloy as TES materials, and have conducted a lot of research. [19][20][21][22][23][24] For instance, Faik et al 25 investigated the structure and thermophysical properties of Zn 85.8 Al 8.2 Mg 6 and Mg 70 Zn 24.9 Al 5.1 eutectic alloys, and found that the great potential of the alloys studied in heat energy storage applications. Fang et al 26 calculated Mg-Bi phase change alloy as TES material and found that Mg-54%Bi alloy has high melting enthalpy and activation energy, among which the activation energy is as high as 1322.8 kJÁmol −1 .…”
Section: Introductionmentioning
confidence: 99%